Pengaruh Pola Asuh Terhadap Status Gizi Anak - Hasrul Hasrul; Hamzah Hamzah; Aslinda Hafid (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
The background of nutritional status is the expression of a state of balance in the form of a certain variable or manifestation of nutriture in the form of certain variables, optimal nutritional status is the balance between intake and need for nutrients. Method; The research used is descriptive-analytic using multiple regression analysis approaches, with a sample size of 30 respondents. Result; There is no significant effect between parenting styles of parents on the nutritional status of elementary school children, the value is 0. 551> 0.05. Conclusion; that there is no effect of parenting style on the nutritional status of elementary school children. In developing information that has a contribution to science, especially in nursing education about the nutritional status of children.